EFFECT OF CHANGE IN SALINITY ON THE SURVIVAL OF PENAEUS MONODON (FABRICIUS) POSTLARVAE. - Chakraborty, R K; Bhowmik, M L; Halder, D D (Indian Journal of Fisheries, 2011)
To assess the effect’of sudden change in salinity on the postlarvae on direct stocking or during gradual change in monsoon months, experiment was conducted in the laboratory. Results indicated that, for a direct change in salinity in the range of 3 to 30 ppt, survival varied between 76 and 100%. During a gradual change from 5 to 0.5 ppt, survival was 68% up to 2 ppt. In both the cases, survival is very poor below 2 ppt salinity